Lessons learned from a pilot study of an Indigenous patient navigator intervention in Queensland, Australia. (17th May 2017) - Bernardes, C.M.; Martin, J.; Cole, P.; Kitchener, T.; Cowburn, G.; Garvey, G.; Walpole, E.; Valery, P.C.
Abstract : Indigenous patient navigator (IPN) programmes show promise in addressing barriers to cancer care and facilitation of patient self‐efficacy. The purpose of this paper is to describe and reflect upon the experience of training an IPN and implementation of the intervention in the Australian context with Indigenous cancer patients. Randomised clinical trial might provide the best available evaluation measure of an intervention but caution should be taken in the implementation process. Socio‐cultural aspects and training can affect the conduct of this type of intervention. We report here five issues needing consideration prior to implementing such intervention. Specifically: (1) recognition of the collective bonds within Indigenous community and understanding by IPN of the degree of personal assistance perceived as not intrusive by the patient; (2) conduct ongoing evaluation of the different role of an IPN involved in this intervention care provider vs. researcher. (3) meaningful engagement develops from a trusting/collaborative relationship between research team and study site staff which may not occur in the study time frame; (4) existing skills as well as training provided may not translate in the IPN understanding and aligning with the study objectives/research values; (5) recruitment of participants requires innovative and highly flexible strategies to be successful.